Analysis of financial statements in measuring the performance of UMKM in Mamuju Regency (Case Study on the AL-KAHFI FOOD Business Group) - Krisna Mutiara Wati (ProBisnis : Jurnal Manajemen, 2023)
Financial reports provide an overview of the company's financial position, operational performance and cash flow. Financial statement analysis helps MSME owners identify their business strengths and weaknesses, and evaluate their financial performance objectively. The Al Khafi Food Business Group is a business group formed by the government in an effort to drive the community's economy in post-earthquake areas in Mamuju Regency. Based on the discussion of the performance of the AL-KAHFI FOOD Business Group's UMKM, it has shown good performance as measured by the financial reports from 2021-2022. The value of each measurement (NPM, ROE, GPM) shows an increasing trend. However, along with this increase, the AL-KAHFI FOOD business group also needs to consider a long-term strategy to maintain and improve their financial performance in a sustainable manner, including product diversification, increasing operational efficiency, innovation and developing new markets